Compensation for Expropriation in Ethiopia and the UK: A Comparative Analysis - Weldegebriel, Daniel Ambaye (Bahir Dar University Journal of Law, 2022)
Land expropriation, also known as compulsory purchase in the UK, is a common practice both in the UK and Ethiopia. The purpose of this paper is to compare and contrast the valuation systems and compensation methods used in Ethiopia and the UK in a bid to establish the levels of compensation paid to those who have lost their property in the interest of society. The method employed is micro-comparison, as opposed to macro-level comparison which focuses on the general aspect of comparison of two legal systems. The findings of this study show that the principle of compensation as â€œthe full recompense of the property lostâ€ has been observed in the UK, while this has not been the case in Ethiopia, mainly because the land has no value to the holder.